X-Shooting ULLYSES: massive stars at low metallicity : XIII. testing the bi-stability jump in the Large Magellanic Cloud - Alkousa, Thaer; Crowther, P. A.; Bestenlehner, J. M.; Sana, H.; Tramper, F.; Vink, J. S.; Pauli, D.; Loon, J. Th van; Najarro, F.; Kuiper, Rolf; Sander, Andreas A. C.; Bernini Peron, Matheus (Astronomy and astrophysics, 2025)
Context: Massive stars (8 M⊙) play an important role in galactic evolution at all cosmic ages. A deeper understanding of the behaviour of mass loss in low metallicity environments is therefore required. This behaviour largely determines the path of a massive star throughout its life, and its final fate. A better understanding would allow us to predict the evolution of massive stars in the early Universe better. Aims: We investigated the theoretical bi-stability jump, which predicts an increase in the mass-loss rates below Teff ≈25-21 kK. We further constrained the photospheric and wind parameters of a sample of late-O and B supergiants in the Large Magellanic Cloud. Methods: We used the 1D non-local thermal equilibrium radiative transfer model CMFGEN in a grid-based approach and a fine-tuned spectroscopic fitting procedure that allowed us to determine the stellar and wind parameters of each star. We applied this method to ultra-violet data from the ULLYSES programme and to complementary optical data from the XShootU collaboration. We also used evolutionary models to obtain the evolutionary masses, and we compared them to the spectroscopic masses we derived. Results: We derived physical parameters and wind properties of 16 late-O and B supergiants that span a wide temperature range of T sub eff ≈12-30 kK, surface gravity range of log (gcm s−2) ≈1.8-3.1, and mass-loss rate range of Ṁ ˙≈ 10−7.6−10−5.7 M⊙ yr−1. We also compared our results to previous studies that attempted to investigate the metallicity dependence of the wind properties. Conclusions: The photospheric and wind properties we derived are consistent with those of multiple previous studies. The evolutionary and spectroscopic masses for most of our sample are consistent within the uncertainties. Our results do not reproduce a bi-stability jump in any temperature range, but rather a monotonic decrease in the mass-loss rate at lower temperatures. We obtain a relation of the wind terminal velocity to effective temperature for supergiants in the Large Magellanic Cloud of ν∞/km s−1 = 0.076(±0.011)Teff/K − 884(±260). The mass-loss rates we derived disagree with the mass-loss rates predicted by any of the numerical recipes. This is also the case for the ratio of the terminal wind velocity to the escape velocity ν∞/νesc, and we derived the relation ν∞/νesc = 4.1(±0.8) log (Teff/K) −16.3(± 3.5). The wind parameters depend on the metallicity, based on a comparison with a previous study of the Small Magellanic Cloud, and the modified wind momentum-luminosity relation is log DmomLMC = 1.39(±0.54)log(Lbol/L⊙) + 20.4(±3.0).